Outcomes of Neutropenic Patients with Clostridium difficile Infection. (October 2020) - Sharma, Roopali; Dixit, Deepali; Pathickal, Sherin; Park, Jenny; Lee, Bernice; Jain, Siddharth; Kairys, Joelle; Katchiuri, Nino; Park, Tae; Narayanan, Navneeth; Swamy, Siddharth
Abstract : Background: Data from Clostridium difficile infection (CDI) in neutropenic patients are still scarce. Objective: To assess outcomes of CDI in patients with and without neutropenia. Methods: The study included a retrospective cohort of adult patients at 3 academic hospitals between January 2013 and December 2017. The 2 study arms were neutropenic patients (neutrophil count <500/mm 3 ) and nonneutropenic patients with confirmed CDI episodes. The primary outcome evaluated the composite end point of all-cause in-hospital mortality, intensive care unit (ICU) admissions, and treatment failure at 7 days. The secondary outcome evaluated hospital length of stay. Results: Of 962 unique cases of CDI, 158 were neutropenic (59% men) and 804 were nonneutropenic (46% men). The median age was 57 years (IQR, 44–64) in the neutropenic group and 68 years (IQR, 56–79) in the nonneutropenic group. The median Charlson comorbidity score was 5 (IQR, 3–7.8) and 4 (IQR, 3–5) in the neutropenic and nonneutropenic groups, respectively. Regarding severity, 88.6% versus 48.9% were nonsevere, 8.2% versus 47% were severe, and 3.2% versus 4.1% were fulminant in the neutropenic and nonneutropenic groups, respectively. Also, 63% of patients (60.9% in nonneutropenic, 65.2% in neutropenic) were exposed to proton-pump inhibitors. A combination CDI treatment was required in 53.2% of neutropenic patients and 50.1% of nonneutropenic patients. The primary composite end point occurred in 27% of neutropenic patients versus 22% of nonneutropenic patients ( P = .257), with an adjusted odds ratio of 1.30 (95% CI, 0.84–2.00). The median hospital length of stay after controlling for covariates was 21.3 days versus 14.2 days in the neutropenic and nonneutropenic groups, respectively ( P < .001). Complications (defined as hypotension requiring vasopressors, ileus, or bowel perforation) were seen in 6.0% of the nonneutropenic group and 4.4% of the neutropenic group ( P = .574), with an adjusted odds ratio of 0.61 (95% CI, 0.28–1.45). Conclusions: Neutropenic patients were younger and their cases were less severe; however, they had lower incidences of all-cause in-hospital mortality, ICU admissions, and treatment failure. Hospital length of stay was significantly shorter in the neutropenic group than in the nonneutropenic group. Funding: None Disclosures: None